Impact of Corporate Governance in Solving the Challenges Faced by Family Business Transitions: Case Study of Pakistan - Fareeha Zafar, Zara Usmani, (Journal of Medical Biomedical and Applied Sciences, 2014)
This research paper centers on the challenges faced in transferring and sustaining the family business to the next generations in Pakistan. Family businesses are mostly Small and Medium Enterprises SMEâs and our thought to be the backbone of every economy. This paper talks regarding the increasing number of family business in Pakistan. Family businesses are facing many challenges due to the rising growth and globalization of economies. The way businesses tackle with these challenges can be the reason for their success and failure. By incorporating good corporate governance framework and systems many of the challenges can be eradicated. In this paper, the significance of corporate governance in family owned business is identified. This study looks at the theoretical background of corporate governance and its inculcation in the family businesses of Pakistan. Family businesses play a major role for economic growth in Pakistan. This study aims to emphasize that for a sustainable family businesses and their perpetual growth, good corporate governance must be introduced in such entities. In addition to family owners more non-family employees and managers should be hired in the business, so that business is managed more justly and efficiently without any biasness keeping in mind the business laws and codes. Corporate governance will ensure that FOBs are transparent enough to satisfy its various stakeholders such as supplierâs customers and creditors.